Infecção por Toxoplasma gondii e Neospora caninum em cães e lobos-guará: soroepidemiologia e imunodiagnóstico - Silva, Deise Aparecida de Oliveira (2006)
Toxoplasma gondii and Neospora caninum are two closely related apicomplexan parasites, even though phylogenetic, ultrastructural, antigenic and biological differences have been already described. Seroepidemiological studies have demonstrated that T. gondii infection is often in domestic and sylvatic canids, whereas N. caninum infection is less common, but it is epidemiologically relevant because dogs and coyotes are their definitive hosts. This thesis is consisted of five studies on T. gondii and N. caninum infection in dogs (Canis familiaris) and maned wolves (Chrysocyon brachyurus) conducted in the Immunoparasitology Laboratory, Federal University of Uberlândia, with emphasis on seroepidemiology and immunodiagnosis. Different antigen preparations and various serological tests, such as indirect hemagglutination test (IHAT), indirect fluorescence antibody test (IFAT), immunoenzymatic test (ELISA), immunoblotting and immunoprecipitation were developed and employed in different dog and maned wolf populations. The first study established the optimal cut off titers in IFAT (1:16) and ELISA (1:64) for the detection of IgG antibodies to T. gondii in dogs by using the twograph receiver-operating characteristic (TG-ROC) curve and considering the reactivity to the major surface antigen SAG1 as infection marker. The second study developed a capture IgMELISA using heterologous antibodies (anti-human IgM) and showed a transient IgM profile in canine acute toxoplasmosis, whereas the kinetics of IgG antibodies to T. gondii in dogs revealed an early and long-time immune response. T. gondii was demonstrated by mouse bioassay and immunohistochemical assay only from dogs with fatal toxoplasmosis. The third study showed that seropositivity to N. caninum (6.7%) was lower than to T. gondii (36%) in dogs with clinical symptoms, including animals with co-infection (3.1%). The fourth study established the optimal cut off titers in IFAT (1:50) and ELISA (1:200) for the detection of IgG antibodies to N. caninum in dogs by using TG-ROC curve, but ELISA showed low specificity. Immunodominant antigens of N. caninum, especially those below 35 kDa, were weakly inhibited by T. gondii antigens in inhibition immunoblotting, indicating that they are more species-specific antigens. The fifth study showed the occurrence of antibodies to N. caninum in maned wolves (8,5%), even though in lower proportion as compared to T. gondii (74.6%), by using homologous (anti-wolf IgG), heterologous (anti-dog IgG) or affinity (Protein A) conjugates in ELISA or IFAT. Altogether, it can be concluded that the diagnosis of T. gondii infection in dogs should be based on the combination of serological tests, particularly IFAT and ELISA, with emphasis in the determination of antibody titers and classes, such as specific IgM, which was efficiently detected by capture IgM-ELISA using heterologous antibodies. N. caninum infection can be present in dogs from Uberlândia city and should be considered in the differential clinical diagnosis with T. gondii in dogs presenting clinical signs, by using preferentially IFAT and immunoblotting to detect immunodominant antigens. The occurrence of antibodies to T. gondii and N. caninum in maned wolves could be evaluated by homologous, heterologous and affinity conjugates, indicating a relevant exposure of this species to T. gondii and, in lower extension, to N. caninum.